2018
DOI: 10.1186/s12909-018-1277-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patient feedback on the medical performance of qualified doctors: a systematic review

Abstract: BackgroundPatient feedback is considered integral to quality improvement and professional development. However, while popular across the educational continuum, evidence to support its efficacy in facilitating positive behaviour change in a postgraduate setting remains unclear. This review therefore aims to explore the evidence that supports, or refutes, the impact of patient feedback on the medical performance of qualified doctors.MethodsElectronic databases PubMed, EMBASE, Medline and PsycINFO were systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 69 publications
0
47
0
3
Order By: Relevance
“…As there is currently no consensus on the use of critical appraisal in the synthesis of qualitative research, we did not set a priority quality threshold nor did we exclude papers/reports on the basis of quality. Similarly to other systematic reviews, conceptual relevance took precedence over methodological rigour. Appraisal was conducted to improve transparency in the systematic review process.…”
Section: Methodsmentioning
confidence: 99%
“…As there is currently no consensus on the use of critical appraisal in the synthesis of qualitative research, we did not set a priority quality threshold nor did we exclude papers/reports on the basis of quality. Similarly to other systematic reviews, conceptual relevance took precedence over methodological rigour. Appraisal was conducted to improve transparency in the systematic review process.…”
Section: Methodsmentioning
confidence: 99%
“…Integration of patient feedback into performance assessment is fraught with challenges, but if implemented effectively, it could trigger meaningful behavior change and enhance safety and quality in patient care. 65 More research is needed in this important area.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…The idea that reflection will lead to learning and improvement is based on the work of Dewey from the 1930s and continued with models such as Schön and Gibbs designed to support reflective practice . Whether reflection prompts learning and change has been questioned, although some studies have identified changes in behaviour as a direct result of reflection taking place within clinical practice settings . Reflective practice is now mandated for most health professionals, with documented evidence of reflecting on patient and colleague feedback required for continuing professional development and revalidation.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Whether reflection prompts learning and change has been questioned, although some studies have identified changes in behaviour as a direct result of reflection taking place within clinical practice settings. [17][18][19][20] Reflective practice is now mandated for most health professionals, with documented evidence of reflecting on patient and colleague feedback required for continuing professional development and revalidation. Despite the focus on retrospective written reflection, increasingly, arguments are being made that reflection, and in particular reflection in action, should instead be fully embedded within the multiple contexts of clinical practice.…”
Section: Introductionmentioning
confidence: 99%